The Million Hearts Initiative and Cardiovascular Health Equity - Kate Sustersic Gawlik; Cynthia Arslanian-Engoren; Lola A. Coke; Debra K. Moser; Ruth E. Taylor-Piliae (Journal of Cardiovascular Nursing, 2026)
Background: Cardiovascular disease (CVD) is the leading cause of death in the United States, disproportionately affecting populations affected by structural and social inequities. Million Hearts 2027 aims to advance CVD health equity through targeted policies, processes, and practices that promote equitable access to resources. The initiative prioritizes 5 populations at increased risk: racial and ethnic minority groups, individuals with lower incomes, people living in rural areas or healthcare access deserts, individuals with behavioral health conditions who use tobacco, and pregnant or postpartum persons with hypertension. Purpose: To provide registered nurses (RNs) and advanced practice registered nurses (APRNs) with tools, resources, and strategies to effectively partner with these 5 priority populations to reduce cardiovascular risks. Conclusions: Million Hearts has practical, adaptable change packages and action guides that translate evidence-based cardiovascular prevention strategies into clinical and community settings. It addresses both clinical risk factors and upstream social drivers of health among populations disproportionately affected by CVD. RNs and APRNs are uniquely positioned to implement these strategies through patient education, screening, chronic disease management, care coordination, and advocacy, to reduce cardiovascular morbidity, mortality, and health inequities. Clinical Implications: Registered Nurses and APRNs play a critical role in advancing equitable cardiovascular care. The use of the Million Hearts change packages and action guides focused on hypertension control, tobacco cessation, cholesterol management, cardiac rehabilitation, and hypertension in pregnancy can strengthen prevention efforts across diverse settings. Increased awareness and implementation of these tools support nurse-led interventions, interprofessional collaboration, and improved cardiovascular outcomes among vulnerable and underserved populations.